Integrating breeding, feeding and keeping systems in the Lowland Livestock-Crop Agriculture Developing Centre; perspectives from West Papua (Agroindustrial Science, 2026)
The integration of breeding, keeping, and feeding practices is essential for improving livestock productivity and sustainability, particularly in lowland agricultural systems. This study investigates the integration of these practices in the Lowlands Agriculture Development Centre of Manokwari, West Papua. Using Principal Component Analysis (PCA) and hierarchical clustering, key factors influencing livestock performance were identified, including grazing systems, reproductive strategies, feeding types, and shelter management. The principle finding shown majority of livestock are of local breeds, followed by crossbred and wild types. This suggests a dominance of indigenous stock over improved or exotic breeds. The number of offspring/parents, births/parent/year, mating system, management system, feed type, and feeding frequency are significant factors influencing livestock outcomes. Wild livestock, natural mating, and artificial insemination significantly impact livestock performance. This result highlights the dominance of traditional practices such as natural mating and the use of local feeding resources, alongside significant variations in sheltering and grazing systems. Livestock relies mainly on agricultural or plantation products, while commercial feed and household waste are minimally used. Two distinct clusters of livestock management were revealed, indicating varying levels of efficiency and sustainability among farmers. This research emphasizes the importance of adopting integrated approaches to optimize livestock management, enhance productivity, and support sustainable agricultural development in tropical lowlands. The findings provide actionable insights for policymakers and practitioners in the region.
Keywords: Livestock management; Feeding strategies; Lowland agriculture; Sustainability; Agricultural development